Evaluation of the predictive power of laboratory markers in the diagnosis of acute appendicitis in the elderly - Savaş Bayrak; Cihad Tatar; Ekrem Çakar; Sukru Colak; Mehmet Emin Gunes; Kemal Tekeşin; Bünyamin Gürbulak; Erdem Kinaci; Mert Mahsuni Sevinc (İstanbul Kuzey Klinikleri, 2019)
INTRODUCTION[|]The aim of this study was to analyze the predictive value of preoperative laboratory findings in acute appendicitis in geriatric patients aged >65 years.[¤]METHODS[|] We enrolled a total of 4121 patients. A retrospective evaluation of the demographic features was made using preoperative laboratory values such as the white blood cell (WBC), neutrophil, and lymphocyte counts; platelet counts; the mean platelet volume and bilirubin values; and postoperative pathological data of the patients from the electronic file system. The neutrophil-to-WBC and neutrophil-to-lymphocyte ratios were calculated. Patients were divided into two groups, as geriatric (≥65 years old, n=140) and non-geriatric (<65 years old, n=3981).[¤]RESULTS[|]The white blood cell and lymphocyte counts, and the neutrophil-to-WBC ratio, were significantly higher in the non-geriatric group (p<0.001, p=0.013, and p=0.021, respectively). The neutrophil and platelet counts were higher in the non-geriatric group, but this difference was not statistically significant (p=0.073 and p=0.072, respectively). A higher neutrophil-to-lymphocyte ratio was determined in the geriatric group, but the difference was not significant (p=0.176). According to the optimumal cutoff value of 12.11×103/µL for WBC, specificity and sensitivity values of 65.4% and 57.9% were calculated, respectively; the AUC value was 0.632+-0.024 (p<0.001). A receiver operating characteristic (ROC) analysis was used to calculate the optimum cutoff values of neutrophil-to-WBC ratio, lymphocyte, and the mean platelet volume, but the diagnostic accuracy of these tests was inadequate with an AUC of <0.6.[¤]DISCUSSION AND CONCLUSION[|]WBC values >12.11×103/µL were predictive of acute appendicitis in geriatric patients. The other parameters were not predictive, and further studies are required.[¤]